Fetal macrosomia Maternal and Perinatal outcome - Al - Wazzan*, Raida Muhammed; Sarsam, Samar Daoud (AL-Kindy College Medical Journal, 2011)
Background: Fetal macrosomia represent acontinuing challenge in obstetrics and increasing init's occurrence as well as it is associated with maternaland perinatal complications.Objective : To determine the maternal and perinataloutcome related to fetal macrosomia.Design: A prospective case control study.Patients and methods) :10th March-31st May, 2006A prospective case control study had done over theperiod from 10th March to 31st May, 2006 in Al-Batoolmaternity teaching hospital in Mosul city .The studygroup consisted from 633 singleton alive newbornswith gestational age ≥37weeks weighing 4000 gramsand heavier and mothers of these newborns comparedwith control group which consisted from 4155singleton alive newborn with gestational age≥37weeks weighing 2500-3999 grams and mothers ofthese newborns .The obstetrical outcome variableswhich compared between the two groups include modeof delivery, indication of caesarean section andmaternal and perinatal complications.Results :Macrosomic newborns (≥4000grams) delivered in thisstudy account for (12.45%) of total deliveries.Newborns with a birth weight of ≥4500gramsconstitute 2.65% from all deliveries .Male Newborns(65.24%) was higher and statistically differed amongthe study group (p value=0.001).Instrumental vaginal delivery (P value=0.010,Oddratio :2.12, 95 %CI :1.19-3.76) and cesarean sectiondelivery (P value=0.000,Odd ratio:1.63, 95 %CI :1.34-1.98), mainly the emergency cesarean section(18.79%), were significantly different among thestudy group .Failure of progress of labour andcephalopelvic disproportion were the main indicationsin study group and showed statistical significantdifference between the two groups.Among the study group, there was neither maternaldeath nor uterine rupture but there was higheroccurrence of postpartum hemorrhage, genital tracttrauma and shoulder dystocia which were significantlydifferent when it compared with control group .Erb'spalsy was the main perinatal complication and wasstatistically different among macrosomic group (Pvalue=0.000) .Conclusion: Fetal macrosomia was associated withhigher rate of instrumental vaginal delivery andcaesarean section mainly due to failure of progress oflabour and cephalopelvic disproportion .There werehigher rate of postpartum haemorrhage, genital tracttrauma as well as shoulder dystocia with neithermaternal death nor uterine rupture in study group .Among macrosomic newborn, Erb's pulsy was themain perinatal complication